(untitled) (Revista de Ciências Agroveterinárias, 2013)
The aim of this research was to evaluate the severity of alternaria leaf spot (Alternaria helianthi) in sunflower crop sown in different densities. The experiments were conducted at the Ressacada Experimental Farm, Florianopolis, SC, Brazil, on the crop season of 2009/2010. Sowing was done at a spacing of 0.5 and 1.0 m between the rows, keeping 3.7, 4.9, 5.7 and 6.6 plants per meter, resulting in 74,000; 98,000 ; 114,000 and 132,000 plants per hectare to 0.5 m between the tree rows and 37,000; 49,000; 57,000 and 66,000 plants per hectare for the spacing of 1.0 m. The experimental design was in randomized blocks in a 4 x 2 factorial (four seeding rates and two row spacings) with three replicates. The severity was assessed based on diagrammatic scale for specific alternaria leaf spot in sunfl ower. The results indicated no interaction between the levels of severity with the variation of line spacing and distribution of plants on line, but showed effect of the distribution of plants on line in the severity, with the higher plant density in the line showed a higher severity, for the both spacing in the lines planting.